PERSISTENT HEPATOCELLULAR SECRETORY FAILURE: A RARITY IN HEPATOLOGY - Ali, Faisal; Butt, Muhammad Abdurrahman; Ahmed, Ibrahim; Rao, Bassam; Salih, Mohammad (Journal of Ayub Medical College Abbottabad, 2024)
Persistent hepatocellular secretory failure (PHSF) is a rare condition that presents as elevated bilirubin despite treatment and elimination of all possible causes, including intrahepatic and extrahepatic biliary obstruction. Very limited literature is available regarding this condition, highlighting its rarity. A 65 years old male who was diagnosed with symptoms of cholestasis. He was diagnosed with pancreatic adenocarcinoma leading to obstructive jaundice. He underwent endoscopic retrograde cholangiopancreaticography and self-expandable metallic stent (SEMS) placement in the common bile duct. Despite SEMS placement, he complained of persistent jaundice, pale stools and itching. His bilirubin was persistently elevated and imaging showed patent stent. After a thorough work-up and discussion in a multidisciplinary team meeting, he was diagnosed as a case of PHSF. The patient is being managed conservatively with ursodeoxycholic acid and cholestyramine. His liver function tests improved after addition of rifampin.